Impact of 24/7/365 Attending Radiologist Coverage on the Turnaround Time in an Emergency and Trauma Radiology Department. Issue 3 (August 2021) - Jalal, Sabeena; Ouellette, Hugue; Ante, Zharmaine; Munk, Peter; Khosa, Faisal; Nicolaou, Savvas
Objective: To study the impact of 24/7/365 attending radiologist coverage on the turnaround time (TAT) of trauma and nontrauma cases in an emergency and trauma radiology department. Patients and Methods: This was a retrospective chart review in which TAT of patients coming to the emergency department between 2 periods: (1) December 1, 2012, to September 30, 2013, and (2) January 1, 2017, to January 30, 2018, and whose reports were read by an attending emergency and trauma radiologist was noted. Results: The 24/7/365 radiology coverage was associated with a significant reduction in TAT of computed tomography reports, and the time reduction was comparable between trauma and nontrauma cases. In adjusted models, the extension of radiology coverage was associated with an average of 7.83 hours reduction in overall TAT (95% confidence interval [CI]: 7.44-8.22) for reports related to trauma, in which 2.73 hours were due to reduction in completion to transcription time (TC; 95% CI: 2.53-2.93), and 5.10 hours were due to reduction in transcription to finalization time (TF; 95% CI: 4.75-5.44). For reports related to nontrauma cases, 24/7/365 coverage was associated with an average of 6.07 hours reduction in overall TAT (95% CI: 3.54-8.59), 2.91 hours reduction in TC (95% CI: 1.55-4.26), and 3.16 hours reduction in TF (95% CI: 0.90-5.42). Conclusion: Our pilot study demonstrates that the implementation of on-site 24/7/365 attending emergency radiology coverage at a tertiary care center was associated with a reduced TAT for trauma and nontrauma patients imaging studies. Although the magnitude and precision of estimates were slightly higher for trauma cases as compared to nontrauma cases. Trauma examinations stand to benefit the most from 24/7/365 attending level radiology coverage.